Cultivating Critical Thinking Skill In Teaching And Learning And Learning Process - Yahaya, Azizi (2008)

(untitled)
The purpose of this article is to spearhead two objectives namely, to fulfill my assignment and to help our future leaders that are our beloved student to analyze multilogical problem of contemporary in teaching and learning process . Those problem that can be viewed holistically from the top or bird eyes perspective thus manages them using correct tool and try solve from many different angles. Joanne Kurfiss simply define critical as “ An investigation whose reason is to explore problem to arrive at the hypothesis that integrate all available information convincingly justified. It is a self regulatory which result in interpretation, analysis, evaluation and inference as well as explanation of evidence, conceptual, methodological or conceptual consideration upon which the judgment is base.